Representation of Inner Conflict in Maryam Touzani's Film The Blue Caftan: A Kurt Lewin Literary Psychology Study - Haekal Maulana Zaki; Edi Komarudin; Khomisah Khomisah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to analyze the representation of inner conflict in Maryam Touzani's film The Blue Caftan using Kurt Lewin's psychological conflict theory within the framework of literary psychology. This research employed a descriptive qualitative method with a literary psychology approach. The data consisted of dialogues, actions, expressions, and scenes representing the characters' inner conflicts in the film. Data were collected through observation and note-taking techniques, while data analysis was conducted by identifying, classifying, interpreting, and describing the forms of inner conflict based on Kurt Lewin's theory. The findings reveal that no approach–approach conflict was identified, while two avoidance–avoidance conflicts and five approach–avoidance conflicts were found. These conflicts are represented through the psychological experiences of the three main characters, Halim, Mina, and Youssef, as they face dilemmas related to moral responsibility, interpersonal relationships, social pressure, economic conditions, and the acceptance of life's realities. This study demonstrates that Kurt Lewin's psychological conflict theory provides a more specific framework for explaining the representation of inner conflict in film and contributes to the development of literary psychology studies, particularly those focusing on contemporary Moroccan cinema.